Impact of endoscopic ultrasound-guided biliary drainage on the management of difficult biliary cannulation in patients with distal malignant biliary obstruction - Spadaccini, Marco; Binda, Cecilia; Mauro, Aurelio; Legros, Romain; Colombo, Matteo; Giacchetto, Marco; Andreozzi, Marta; Carrara, Silvia; Ramai, Daryl; Albouys, Jérémie; Mazza, Stefano; Coluccio, Chiara; Facciorusso, Antonio; Fabbri, Carlo; Anderloni, Andrea; Hassan, Cesare; Jacques, Jérémie; Repici, Alessandro; Fugazza, Alessandro (Endoscopy, 2025)
Biliary drainage in patients with distal malignant biliary obstruction (DMBO) carries a higher risk of difficult biliary cannulation (DBC) during endoscopic retrograde cholangiopancreatography (ERCP). After the failure of standard cannulation, endoscopists may proceed with advanced cannulation techniques and/or with endoscopic ultrasound-guided biliary drainage (EUS-BD).This was a retrospective study of consecutive patients with DMBO and a dilated common bile duct (CBD; >12 mm) who underwent ERCP for endoscopic biliary drainage in four European centers. The rates of DBC, technical and clinical success, and procedure-related adverse events (AEs) were assessed. The predictive factors for AEs were also investigated through regression analysis. The EUS-BD approach was considered either as the first option after standard cannulation failure or as the final option after advanced cannulation failure.1016 patients with DMBO were included in the study, with 524 (51.6%) matching the definition of DBC. Clinical success was achieved in 956 patients (94.1%). Procedure-related AEs were experienced by 167 patients (16.4%). Patients with DBC had a higher risk of AEs (P=0.003); however, patients undergoing “early” EUS-BD showed a risk of AEs comparable with those managed with standard cannulation (P=0.38). An attempt at any advanced cannulation technique was independently associated with the occurrence of AEs (P=0.001).The risk of AEs is higher in patients with DMBO and DBC, this appears to be mainly related to the advanced cannulation techniques. In patients with a dilated CBD (>12 mm), “early” EUS-BD may minimize the risk of AEs.